2018
DOI: 10.1111/jdi.12778
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate and patient characteristics of severe hypoglycemia in treated type 2 diabetes mellitus patients in Japan: Retrospective Diagnosis Procedure Combination database analysis

Abstract: Aims/IntroductionTo evaluate the incidence rate of and identify factors associated with severe hypoglycemic episodes in patients with treated type 2 diabetes mellitus.Materials and MethodsUsing Diagnosis Procedure Combination hospital‐based medical database, we carried out a retrospective cohort study to assess the incidence rate of severe hypoglycemia in treated type 2 diabetes mellitus patients. We evaluated the associations between severe hypoglycemia and age, sex, complications, and current use of insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
2
18
2
Order By: Relevance
“…There was a significant difference in the hypoglycemia episodes, as con irmed by the student t-test (4.06368) at a p value = 0.000147. These results are also aligned with previous studies like a retrospective study conducted in Japan, which indicated multiple factors like age, cognitive decline, combinational therapy with of Insulin and Sulphonylureas have been cited as risk factors for severe hypoglycemia (Ikeda et al, 2018).…”
Section: Higher Cognitive Derangement In Oha and Insulin Combinationasupporting
confidence: 90%
See 1 more Smart Citation
“…There was a significant difference in the hypoglycemia episodes, as con irmed by the student t-test (4.06368) at a p value = 0.000147. These results are also aligned with previous studies like a retrospective study conducted in Japan, which indicated multiple factors like age, cognitive decline, combinational therapy with of Insulin and Sulphonylureas have been cited as risk factors for severe hypoglycemia (Ikeda et al, 2018).…”
Section: Higher Cognitive Derangement In Oha and Insulin Combinationasupporting
confidence: 90%
“…In a retrospective study conducted in Japan, multiple factors like age, cognitive decline, combinational therapy with of Insulin and sulphonylureas have been cited as risk factors for severe hypoglycemia. (Ikeda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…40 Microvascular complications cluster within individuals with type 2 diabetes because of shared pathophysiology 41 and have all been associated with severe hypoglycaemia in large population-based studies of type 2 diabetes. 42 Despite strong bivariate associations between both peripheral sensory neuropathy and retinopathy and incident severe hypoglycaemia in the present study, neither was an independent risk factor in multivariable models. This may have reflected the availability of plasma NT-proBNP concentrations in the FDS2 but not the FDS1.…”
Section: Discussioncontrasting
confidence: 69%
“…The current study shows that diabetic complications were a strong predictor for hypoglycemia (OR, 2.74; 95% CI, 1.70 to 4.42). It is well-established from different published studies that the micro and macro complications of diabetes, in addition to infection, are considered predisposing variables for severe hypoglycemia [20,25]. In this study, patients with diabetic foot were three times more likely to have hypoglycemia (OR, 3.70; 95% CI, 1.60 to 8.54).…”
Section: Discussionmentioning
confidence: 64%